Antibiotic resistance in grass and soil. (19th February 2019) - Tyrrell, Ciara; Burgess, Catherine M.; Brennan, Fiona P.; Walsh, Fiona
Abstract : Antibiotic resistance is currently one of the greatest threats to human health. The global overuse of antibiotics in human medicine and in agriculture has resulted in the proliferation and dissemination of a multitude of antibiotic resistance genes (ARGs). Despite a large proportion of antibiotics being used in agriculture, little is understood about how this may contribute to the overall antibiotic resistance crisis. The use of manure in agriculture is a traditional and widespread practice and is essential for returning nutrients to the soil; however, the impact of continuous manure application on the environmental microbiome and resistome is unknown. The use of antibiotics in animal husbandry in therapeutic and sub-therapeutic doses creates a selective pressure for ARGs in the gut microbiome of the animal, which is then excreted in the faeces. Therefore, the application of manure to agricultural land is a potential route for the transmission of antibiotic-resistant bacteria from livestock to crops, animals and humans. It is of vital importance to understand the mechanisms behind ARG enrichment and its maintenance both on the plant and within the soil microbiome to mitigate the spread of this resistance to animals and humans. Understanding this link between human health, animal health, plant health and the environment is crucial to inform implementation of new regulations and practice regarding antibiotic use in agriculture and manure application, aimed at ensuring the antibiotic resistance crisis is not aggravated.